Enteric microbiota–gut–brain axis from the perspective of nuclear receptors - Duszka, Kalina (2018)
Nuclear receptors (NRs) play a key role in regulating virtually all body functions, thus maintaining a healthy operating body with all its complex systems. Recently, gut microbiota emerged as major factor contributing to the health of the whole organism. Enteric bacteria have multiple ways to influence their host and several of them involve communication with the brain. Mounting evidence of cooperation between gut flora and NRs is already available. However, the full potential of the microbiota interconnection with NRs remains to be uncovered. Herewith, we present the current state of knowledge on the multifaceted roles of NRs in the enteric microbiota–gut–brain axis.